ECONOMIC MELT DOWN AND DECLINE IN PINEAPPLE PRODUCTION: DETERMINANT OF PRODUCTION INEFFICIENCY OF PINEAPPLE-BASED ALLEY CROPPING PRACTICES IN CROSS RIVER STATE, NIGERIA - I. B. Adinya; S. M. Afu; J.U. Ijoma (Journal of Animal and Plant Sciences, 2010)
This study was carried out to determine production inefficiency of pineapple –based alley cropping practices in Cross River State, Nigeria. A total of 120 pineapple-based alley croppers (farmers) were randomly selected from Cross River Agricultural Zones, using a multi-stage stratified random sampling technique. Multiple regression analysis model was the main tool of data analysis where different functions were used. The results indicated that Cobb-Douglas production function had the best fit in explaining the relationship between output of pineapple and inputs used, the co-efficient of multiple determinant(R2 = 0.58) indicated that fifty-eight per cent of variability in output of pineapple is explained by the independent variables. The F-value of 17.26 indicates that the overall significance of the model at 1per cent level, indicating that there is a significant linear relationship between the independent variables taken together and yield of pineapple produced in Cross River State. The results also indicates that farmers’ education level positively influence their level of production efficiency in pineapple production in the study area. There existed production inefficiency. Extension agents should train pineapple farmers to improve on production technique. There is need to urge Government for the effective implement of action –research type of programme so as to integrate institutional-technical and socio –economic aspects of pineapple base-alley cropping systems as well as post harvest and marketing aspects either through cooperatives or export processing zones.
Keywords: Economic melt down; Production inefficiency; Alley cropping; Cobb-Douglas; Pineapple; Soil fertility management